Simultaneous bifocal and asymptomatic intramuscular nodular fasciitis of the thigh: A case report. Issue 7 (22nd April 2020) - Sukpanichyingyong, Sermsak; Matsumoto, Seiichi; Ae, Keisuke; Tanizawa, Taisuke; Hayakawa, Keiko; Funauchi, Yuki; Minami, Yusuke; Saito, Masanori; Yamashita, Kyoko
Abstract: Nodular fasciitis (NF) is a rapid‐growth benign that is misdiagnosed as sarcoma and leads to overtreatment. The spontaneous regression of NF is a possible phenomenon. "Wait and see" ideal is one of the treatment strategies of NF. Abstract : Nodular fasciitis (NF) is a rapid‐growth benign that is misdiagnosed as sarcoma and lead to overtreatment. The spontaneous regression of NF is a possible phenomenon. "Wait and see" ideal is one of the treatment strategies of NF.